Yield and Nutritional Response of Greenhouse Grown Tomato Cultivars to Sustainable Fertilization and Irrigation Management - Stoleru, Vasile (Plants (Basel), 2020)
Tomato is considered one of the most important crops worldwide from nutritional and economic standpoints, and, in this respect, sustainable production should be a prime objective, particularly in terms of fertilization and irrigation management. The aim of this study was to compare the effects of two fertilization types (chemical or organic) and two irrigation regimes (67% or 100% of evapotranspiration replenishment) on biometrical, biochemical, and yield parameters of three indeterminate cultivars of tomato grown in a greenhouse. The results showed that the effect of organic fertilization was better compared to chemical fertilization for lycopene accumulation and antioxidant activity, as well as for the lower concentrations of any of the macroelements in the tomato fruits; therefore, organic fertilization can be used as an alternative to chemical fertilization in sustainable horticulture. In each cultivar under the same fertilization type, the effect of irrigation was significant on yield and the number of fruits, but the 100% evapotranspiration restoration did not enhance the fruit concentration of all the macroelements and microelements compared to 67% irrigation regime. Higher concentrations of macro- and microelements in the chemically fertilized fruits compared to the organic ones, regardless of the cultivar and the irrigation regime, suggest that the inorganic substances are more easily absorbed by plants under a protected environment. Organic fertilization positively affected the lycopene and antioxidant activities of tomato fruits, thus proving to be a valuable alternative to chemical fertilization in sustainable agriculture, although the product premium quality also depends on the cultivar used.